The Psychosocial Effect of Parental Cancer: Qualitative Interviews with Patients' Dependent Children - Elise S. Alexander; Moira O'Connor; Georgia K. B. Halkett (MDPI AG, 2023)
Background: Children living with parental cancer are at an increased risk for various psychosocial, emotional, and behavioural problems. However, research regarding how children are affected by their parent's diagnosis is still developing and patients' children are typically invisible in clinical practice. This study aimed to investigate how children are affected by their parent's cancer diagnosis, from children's perspectives. Methods: Informed by methods of grounded theory and embedded within a social constructivist framework, twelve children (ranging from 5 to 17 years) living with a parent with cancer were interviewed using a semi-structured format assisted by a novel approach derived from play- and art-based developmental literature. Results: Findings indicate that patients' children are constantly worried and distressed, and there are barriers that can be overcome to mitigate this. Four overarching themes were identified: (I) Feeling worried and distressed; (II) Comprehending their parent's cancer diagnosis; (III) Being disconnected from their supports; and (IV) Needing someone to talk to. Conclusions: Children experience considerable levels of ongoing worry and distress when a parent is diagnosed with cancer and have difficulties comprehending and articulating this. They also feel a level of disconnection from their usual support systems (e.g., parents) and are limited regarding who they can seek out and talk to. Mitigating children's ongoing worries and distress by promoting the availability and accessibility of parents and other supports to children, and reducing communication barriers between children and adults, should be a primary focus of psycho-oncology research and practice.